Sistem Pembaca Citra Kode UPC 128c Berkecepatan Tinggi dengan Linear Scanning, Thresholding, dan Scaling (LTS) - Maryanto, Eddy (JUITA: Jurnal Informatika, 2016)
The aim of this research is to develop and test UPC code 128C image reader built based on LTS Algorithm (Linear scanning, Thresholding, Scaling) invented by Eddy Maryanto in 2010. Software that is used to implement the barcode reader is Borland Delphi 6. Two hundred barcode images is used in testing process. The result of the testing process shows that the system has high enough reading accuracy level i.e about 66% and has ability to read rotated barcode image with high enough accuration. The system has reading rate of 4,69 second per barcode image with threshold multiplier range value of 1,00-1,50.